Integrated economic and sexual and reproductive health programming among married and unmarried adolescent girls in Nigeria: Results from a quasi-experimental cohort study - Mary Phillips; Roselyn Odeh; Meghan Cutherell; Abednego Musau; Claire W. Rothschild; Albert Tele; Jenna Grzeslo; Alexis Coppola; Yusuf H. Wada; Noel Tonka; Alhaji Alhassan Bulama; Kehinde Atoloye; et al. (PLoS ONE, 2025)
Adolescent girls in sub-Saharan Africa are disadvantaged in nearly every measure of well-being when compared to their male peers, resulting in worse health outcomes and lower economic activity. Economically empowering adolescent girls is one approach to improving girls’ wellbeing. Community-based groups that offer girls holistic support, such as increasing income generating capacity, fostering critical thinking, and building support for economic activity among their influencers, have been shown to improve economic and psychosocial assets. This paper describes the results of integrating economic empowerment programming into an existing sexual and reproductive health program for adolescent girls aged 15–19 in Kaduna and Ogun states in Nigeria. Outcomes of interest included increases in income generation and asset purchasing, improved decision-making around use of income and savings, and greater contribution to household expenditures as well as increases in contraceptive use and intention to use contraception in the future. The study was a quasi-experimental design consisting of an intervention group receiving the combined SRH and economic empowerment intervention and a concurrent comparison group receiving only the SRH intervention. Data was collected concurrently in both groups before participants were involved in the intervention (baseline) and nine months after (endline) for the same participants. Results varied by state, with exposure to the intervention associated with increases in the proportion of participants earning money (35pp increase in Kaduna, 58pp increase in Ogun) and almost equal increases in contributions to household expenses. Exposure to the intervention was associated with a significant increase in contraceptive use in Kaduna. Further, exposure to the intervention in Ogun was associated with significant increases in purchasing of assets and intent to use contraception in the future which were not observed in Kaduna. The findings suggest that layered economic empowerment programs can have positive outcomes for diverse cohorts of adolescent girls.